PENGARUH PENINGKATAN GELLING AGENT HIDROKSIPROPIL METILSELULOSA TERHADAP EVALUASI FISIK SEDIAAN GEL HAND SANITIZER AIR PERASAN JERUK NIPIS (CITRUS AURANTIFOLIA SWINGLE) - Senny Listy; Ika Agustina; Indri Astuti Handayani; Maylinda Ririn Nugraheni (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
Most hand sanitizers sold on the market contain alcohol as an ingredient to kill germs. Excessive and continuous use of hand sanitizer can cause irritation and cause a burning sensation on the skin. Therefore, the search for alternative hand sanitizer formulations is being carried out, one of which is using natural ingredients. The natural ingredient that can be used is lime juice. Lime fruit contains a number of organic acids such as citric acid which is the main component, then malic acid, lactic acid and tartaric acid which have antibacterial activity. The aim of this research is to determine the effect of increasing the gelling agent hydroxypropyl methylcellulose on the physical evaluation of lime juice (Citrus aurantifolia Swingle) hand sanitizer gel preparations. This type of research is experimental research. The resulting juice was 112.5 mL using a juicer. Organoleptic tests on formulas A, B and C with hydroxypropyl methylcellulose concentrations of 2.5% each; 3.5% and 5% are all clear to opaque in color and have the characteristic smell of lime juice. The homogeneity test for the three formulas did not reveal any coarse grains, which means that the resulting preparations were well dispersed. The pH change did not occur significantly, tested using One Way ANOVA, showing a significance value greater than 0.05 and still meeting the skin pH requirements, namely 4.5-6.5. The viscosity test was carried out with a Brookfield viscometer with a 64 spindle at a speed of 0.5-2 rpm. The change in viscosity in the 2.5% gel formula and 3.5% gel formula was not significant even though the viscosity decreased every week. The 5% gel formula experienced significant increases and decreases in viscosity and still met the standard viscosity value for hand sanitizer gel preparations, namely 2000-4000 cps. This shows that storage time can affect viscosity. The spreadability test meets the spreadability requirements in the range of 5-7 cm. It was concluded that there was an increasing effect of the gelling agent hydroxypropyl methylcellulose on the physical evaluation of lime juice (Citrus aurantifolia Swingle) hand sanitizer gel preparations. Key words: Gel preparation, hand sanitizer, HPMC, lime